Concurrent changes in eccentric hamstring strength and knee joint kinematics induced by soccer-specific fatigue. (May 2019) - Greig, Matt
Abstract: Objectives: To investigate the influence of soccer-specific fatigue on concurrent changes in knee joint kinematics and hamstring strength, given the increased risk of injury during the latter stages of match-play and the prevalence of knee joint and hamstring muscular injury. Design: Repeated measures, randomized order trials. Setting: Laboratory. Participants: Ten male professional soccer players. Main outcome measures: Reactive inversion, eversion and neutral hop tasks were completed at 15 min intervals during a soccer-specific protocol, with touchdown knee joint kinematics in the frontal and sagittal planes calculated at 200 Hz. In a separate trial, players completed maximal eccentric knee flexions at 160°·s −1 (reflecting average knee angular velocity in the functional task) at 15 min intervals, quantifying peak torque. Results: All trials were characterized by knee varus at touchdown, with ∼4° greater mal-alignment elicited over the final 15 min of the protocol ( P ≤ 0.05). Peak eccentric hamstring strength was significantly ( P = 0.045) reduced throughout the 2nd half. Conclusions: The coincident impairment of eccentric hamstring strength and increased knee varus at touchdown predisposes the player to injury, supporting epidemiological observations. Knee varus in these elite male players is in marked contrast to the valgus associated with ACL injury risk in female players. Highlights: Soccer-specific fatigue reduced peak eccentric knee flexor torque in elite male soccer players. Concurrent changes were observed in knee joint kinematics. Knee varus at landing increased with fatigue. Inversion hopping trials elicited the largest knee varus.